Cutaneous lupus erythematosus: a review of new and emerging therapies - Joana Xará; Margarida Gonçalo (Revista da Sociedade Portuguesa de Dermatologia e Venereologia)
Cutaneous lupus erythematosus (CLE) is an autoimmune connective tissue disorder with heterogenous skin manifestations. According to the current therapeutic guidelines for the treatment of CLE, short courses of topical corticosteroids remain the first-line treatment for localized disease, while topical calcineurin inhibitors offer a safer alternative with lower side effects. Regardless of CLE subtype, antimalarials are the first-line systemic treatment for disfiguring and widespread skin lesions and prevent systemic involvement. In addition, the use of systemic corticosteroids should be restricted to patients with highly active and/or severe CLE. Second-line treatments include methotrexate, retinoids, and dapsone, while mycophenolate mofetil is considered third-line option. Moreover, thalidomide should be reserved for use in recalcitrant CLE patients, preferably in combination with antimalarials. Despite the considerable impact of CLE on quality of life, therapeutic options remain insufficient and, aside from hydroxychloroquine and corticosteroids, no other systemic treatments are approved. This review offers a brief overview of CLE pathogenesis and the current development landscape for new and emerging systemic therapies, highlighting promising targeted drugs such as anifrolumab (anti-type 1 interferon), deucravacitinib (allosteric tyrosine kinase 2 inhibitor), litifilimab (plasmacytoid dendritic cell-targeted therapy), iberdomide (cereblon-targeting ligand), and belimumab (B-cell targeted therapy), among others.